The Magnetic, Joule’s and Ohmic Effect on Incompressible Viscous Flow Over a Hyperbolic Stretching Circular Cylinder - K. Divya Joseph; P. A. Dinesh (International Journal of Mathematics And its Applications, 2018)
In we study the heat transfer of boundary layer flow of an incompressible viscous fluid over hyperbolic stretching cylinder. The governing nonlinear partial differential equations are converted into ordinary differential equations by using suitable transformations, which are then tackled using the homotopy method. The homotopy method gives us solutions in the form of series. The influence of the Magnetic, Joule's and Ohmic effect on velocity as well as temperature profiles are investigated and results can be seen visually in graphs. The computational results without these effects agree excellently with the previous results by [1].